2003
DOI: 10.1161/01.cir.0000072771.11429.83
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel for Coronary Stenting

Abstract: Background-Clopidogrel is administered to prevent stent thrombosis; however, the uniformity of platelet inhibition after treatment and the influence of pretreatment reactivity on drug response have not been described. Methods and Results-Platelet aggregation (5 and 20 mol/L ADP), the activation of glycoprotein IIb/IIIa (PAC-1 antibody), and the expression of P-selectin were measured in patients undergoing elective coronary stenting (nϭ96) at baseline and at 2 hours, 24 hours, 5 days, and 30 days after stenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
381
2
18

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,405 publications
(414 citation statements)
references
References 20 publications
13
381
2
18
Order By: Relevance
“…Previous studies have demonstrated that suboptimal response to antiplatelet agents was affected by many factors 18, 19. Simple linear regression analysis showed that the inhibitory rate of ADP pathway may be associated with age, sex, OSA, hypertension, eGFR, platelet counts and β‐blockers ( P <0.1) (Table S1).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies have demonstrated that suboptimal response to antiplatelet agents was affected by many factors 18, 19. Simple linear regression analysis showed that the inhibitory rate of ADP pathway may be associated with age, sex, OSA, hypertension, eGFR, platelet counts and β‐blockers ( P <0.1) (Table S1).…”
Section: Resultsmentioning
confidence: 91%
“…Suboptimal response to antiplatelet agents or HRPR, in fact, has been associated with an enhanced risk of major cardiovascular events and acute ischemic complications, especially with clopidogrel, where a high HRPR has been described in almost 30% of patients 18, 25, 26. In patients with ACS or undergoing PCI, HRPR is associated with ≈2‐ to 3‐fold greater risk of recurrent ischemic events and about 1.5‐fold greater risk of all‐cause mortality 27, 28, 29.…”
Section: Discussionmentioning
confidence: 99%
“…16 Clopidogrel hyporesponsiveness appears to increase the risk for thrombotic events, particularly in patients undergoing PCI. 17 For instance, the previously mentioned study by Matetzky and colleagues found an increased likelihood of recurrent cardiovascular events among patients with STsegment elevation myocardial infarction (STEMI) who were hyporesponsive to clopidogrel and underwent PCI.…”
Section: Clopidogrelmentioning
confidence: 99%
“…In an initial study designed to examine the uniformity of platelet inhibition by a clopidogrel 300 mg loading dose followed by a 75 mg/day maintenance dose in patients undergoing stenting, platelet function was measured by aggregation and the expression of activation-dependent receptor expression. 1 A normal distribution of response was demonstrated for both measurements. Using a cutpoint of <10% absolute change in aggregation for resistance, the prevalence of resistance was about 50%-60% at 2 h; about 30% at 1 and 5 days; and 15%-21% at 30 days after stenting.…”
Section: Optimizing Clopidogrel Dosingmentioning
confidence: 74%